The importance of Camisea gas in the development of the steel industry in Peru - León Delgado, Elard Felipe (2004)
In the future, the steel industry may be determined by processes of low cost of operation and capital; being the two main routes for the production of steel, the recycling of scrap metal and the reduction of virgin ore. The high reliability and low price of iron ore are the factors that have led to the development of the direct reduction process. In this decision, natural gas is an economical solution for the production of direct reduction products, briquettes and sponge iron. "THE FUTURE IS NOW"